The Future of Quality Measurement in the United States - Yi, Fia (Clinics in Colon and Rectal Surgery, 2014)
The need to practice cost efficient medicine and provide it in the safest way possible is paving the way for quality improvement (QI) programs to take off. American College of Surgeons National Surgical QI Project and Surgical Care and Outcomes Assessment Program are some of the leading examples and have provided useful data to evaluate our systems and decrease morbidity and mortality. With proven outcomes driving morbidity and mortality rates down, we have to wonder how to refine these measures to make them more relevant to specialty surgeries such as colorectal. On the contrary, participation in programs like these has placed extended requirements on hospitals and physicians. In addition, some of the quality measures may be inaccurately identifying low and high performing hospitals and individuals because of inherent flaws in the database. This could potentially be in conflict with the mission of these programs. What will be presented are some alternatives and different directions QI is moving toward.
Keywords: ACS NSQIP; quality improvement; process measures; colorectal surgery